Los juegos didácticos para el desarrollo del pensamiento lógico matemático en los estudiantes de Tercero de Básica de la Unidad Educativa “Adolfo Kolping” en el año lectivo 2022-2023. - Carrasco Chipantiza, Dayana Katherine (2024)
Didactic games are essential for children's learning because they allow them to develop cognitive skills, explore their environment through creativity, develop logical thinking, promote understanding, and resolve everyday problems. This research aimed to determine the importance of didactic games in developing mathematical analytical thinking in thirdgrade students of the Adolfo Kolping Educational Unit in the school year 2022-2023. The methodology had a mixed approach, and its design was non-experimental; the type of research by level was descriptive, by fundamental objective, by field location, and by nature; it was transversal because it took place in a single time and moment. We worked with a population of 500 students, and 20 students were selected as subjects of study in which a non-probabilistic intentional sampling was carried out. The technique used for data collection was observation, in which a ten-question questionnaire was designed, and a test developed in five dimensions was used: abstract thinking, logical reasoning, geometric thinking, metric thinking, and statistical thinking. After performing analysis and results, a summary of the highest percentages of each dimension was elaborated, and it was concluded that didactic games are essential since they are of great help in the development of mathematical and logical thinking when executed in an orderly manner. Therefore, it is recommended that teachers use didactic games since it is vital in mathematics; for many students, this subject is somewhat complex to learn and the one in which they have the most difficulties assuming knowledge. Keywords: didactic games - mathematical, logical thinking, students primary education - mathematics.